Structural and Functional Analysis of Four-Word Lexical Bundles in Academic Book Reviews Published in Q1-Indexed International Journals - Nur Ifadloh; Sri Wuli Fitriati; Widhiyanto Widhiyanto; Dwi Rukmini (JOLLT Journal of Languages and Language Teaching, 2026)
Lexical bundles are an important feature of academic discourse, reflecting textual fluency, information density and rhetorical organization. While there is a massive frame of research on lexical bundles in academic genres, limited research has been done on lexical bundles in academic book reviews, especially in Q1-indexed international journals. The present corpus-based study explores the structural and functional distribution of four-word lexical bundles in academic book reviews published in Q1-indexed international journals. The corpus consists of twenty book reviews taken from ten Q1-indexed international journals. The analysis yielded 37 lexical bundles in this corpus. Structurally, fragments based on prepositional phrases and fragments based on noun phrases dominate the distribution, covering 78.38% of all lexical bundles. These patterns indicate a preference for compact packaging of information in terms of nominal and prepositional structures. In terms of function, the most frequently occurring category was referential bundles (56.75%), followed by discourse-organizing bundles (29.73%), and attitude bundles (13.51%). The prevalence of referential bundles reflects the focus of the genre on elaboration, description and academic evaluation of content, while the relatively low frequency of attitudinal bundles suggests adherence to academic objectivity. In general, the findings of the study reveal a close relationship between the structural patterns and the communicative functions of lexical bundles in the academic book reviews. The study demonstrates the benefits of corpus-based and genre-sensitive approaches for understanding academic discourse and has pedagogical implications for teaching academic writing, particularly in helping students to develop lexical patterns consistent with the standards of academic book reviews.